The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/978-1-4939-7802-1_3
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Freshwater Planarians

Abstract: Planarians are on the rise as a model system for regeneration and stem cell dynamics. Almost in parallel the interest in planarian field biology has declined. Besides representing an independent research discipline in its own right, understanding of the natural habitat is also directly relevant to optimizing culture conditions in the laboratory. Moreover, the current laboratory models are but few of hundreds of planarian species worldwide. Their adaptation to a wide range of ecological niches has resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 171 publications
0
42
0
Order By: Relevance
“…While the sexualization mechanism in this case remains unknown, up-regulation of canonical Wnt pathway activity has been shown to both suppress regeneration and sexualize in other planarian species (Sikes and Newmark, 2013;Sureda-Gómez, Martín-Durán and Adell, 2016). On the basis of these results, Vila-Farré and Rink (2018) have suggested that Wnt pathway activity, which is known to be essential for the regeneration of posterior structures in planaria, may also serve as a switch between gametic and vegetative reproduction. As Wnt is a versatile, early-as well as late-acting regulator of both polarity and cell fate across multicellular animals, confirmation of a mechanistic link between Wnt activity, regeneration, and sexualization outside of the planaria would provide broader evidence for the competitive model proposed here.…”
Section: Germ and Non-germ Lineages Compete For "Spheres Of Influence"mentioning
confidence: 95%
See 4 more Smart Citations
“…While the sexualization mechanism in this case remains unknown, up-regulation of canonical Wnt pathway activity has been shown to both suppress regeneration and sexualize in other planarian species (Sikes and Newmark, 2013;Sureda-Gómez, Martín-Durán and Adell, 2016). On the basis of these results, Vila-Farré and Rink (2018) have suggested that Wnt pathway activity, which is known to be essential for the regeneration of posterior structures in planaria, may also serve as a switch between gametic and vegetative reproduction. As Wnt is a versatile, early-as well as late-acting regulator of both polarity and cell fate across multicellular animals, confirmation of a mechanistic link between Wnt activity, regeneration, and sexualization outside of the planaria would provide broader evidence for the competitive model proposed here.…”
Section: Germ and Non-germ Lineages Compete For "Spheres Of Influence"mentioning
confidence: 95%
“…If non-germline stem cells "win" and suppress germline development, obligate vegetative asexuals that altogether lack specialized germline stem cells, gametes, or gonads, such as the laboratory model planaria Dugesia japonica or Schmidtea mediterranea can be expected. Population variants or close relatives of both of these species are sexual, suggesting that full suppression of germline development is not stable over evolutionary timescales (Sluys and Riutort, 2018;Vila-Farré and Rink, 2018). If, on the other hand, germline stem cells "win" and suppress totipotency in non-germline stem cells, obligate gametic reproducers incapable of WBR can be expected.…”
Section: How Does This Repression Happen?mentioning
confidence: 99%
See 3 more Smart Citations